Metode Pelaksanaan Pekerjaan Pondasi Bore Pile Pada proyek Gedung Baru Instalasi Pelayanan Utama Rumah Sakit Dr Saiful Anwar Malang - Taurina Jemmy Irwanto; Nurul Lia Suryani; Bernessa Veda Ramdha; Abd Rahman; M. Anshori Nurul Ihsan (Jurnal Pengabdian Teknik dan Sains (JPTS), 2023)
The construction stage is a stage that needs attention so that the main goal of producing a quality project can be achieved. In the construction stage, project managers should consider the positive and negative aspects that will occur in the next stage, namely the operational stage. The contractor's profit will be obtained when it is appropriate to apply the construction method at the project site. Different construction methods must also differ in the needs of ny resources, waste generated, and almost certainly differ in the achievement of project objectives in terms of cost, quality, and time.In completing a project to achieve goals effectively and efficiently, a good management system is needed. To implement a good management system, various methods are needed according to the type of building completed. Management develops and directs methods to align resources and equipment use to achieve project objectives. Many factors affect the accuracy of equipment use and resource utilization including cost, time, and and social. To achieve the goal effectively and efficiently, construction management involves the stages of the standard method used in each building (house, building, etc.).